2023
DOI: 10.5603/pjnns.a2023.0009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of SARS-CoV-2 on the nervous system

Abstract: Introduction. The ongoing COVID-19 pandemic is the largest global public health struggle. The spread of the novel coronavirus had resulted in almost 7 million deaths worldwide by January 2023.State of the art. The most common symptoms during the acute phase of COVID-19 are respiratory. However, many individuals present various neurological deficits at different stages of the infection. Furthermore, there are post-infectious complications that can be present within weeks after the initial symptoms. Both the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 78 publications
0
11
1
Order By: Relevance
“…Specifically, we disagree with the subheading 'Neurological symptoms' and the heading given to Table 2: 'Neurological symptoms during acute/post-acute stage of infection in large analyses of patients hospitalised due to COVID-19' [1]. Contradicting these captions, this section and this Table actually discuss neurological disorders rather than neurological symptoms.…”
Section: To the Editorsmentioning
confidence: 81%
See 2 more Smart Citations
“…Specifically, we disagree with the subheading 'Neurological symptoms' and the heading given to Table 2: 'Neurological symptoms during acute/post-acute stage of infection in large analyses of patients hospitalised due to COVID-19' [1]. Contradicting these captions, this section and this Table actually discuss neurological disorders rather than neurological symptoms.…”
Section: To the Editorsmentioning
confidence: 81%
“…We read with interest the review article by Czarnowska et al on the effects of SARS-CoV-2 on the nervous system [1]. The pathophysiology of neuro-COVID has been explained by a systemic immune reaction against the virus (platelet activation, thrombocytopenia, leukocyte activation, overproduction of inflammatory pro-aggregating cytokines, endothelial dysfunction, complement system activation, mast cell activation), microglial activation, cerebral hypoxia, or neuro-invasion of the virus via the olfactory tract, invasion of the virus into the central nervous system via haematogenous pathways, and disruption of the blood brain barrier allowing leukocytes carrying SARS-CoV-2 to enter the brain (the socalled 'Trojan horse' mechanism) [1]. The authors concluded that cerebrovascular disease is the most common neurological complication of SARS-CoV-2 infection [1].…”
Section: To the Editorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations of the virus connected with the highest threat to the population have been named by the World Health Organisation: 'Variants of Concern' (VOCs). Omicron, the current SARS-CoV-2 mutation, has been the most mutated VOC so far [2].…”
mentioning
confidence: 99%
“…The most commonly reported symptoms were shortness of breath when climbing stairs (22.9%), cough (15.4%), and persistent loss of smell and/ /or taste (13.1%) [27]. A post-acute COVID-19 Italian study [2] showed the persistence of symptoms after approximately 60 days from the onset of COVID-19 in 87.4% of 143 patients. Fatigue (53.1%), dyspnoea (43.4%), arthralgia (27.3%) and chest pain (21.7%) were most frequent, with 55% of the patients reporting at least three symptoms.…”
mentioning
confidence: 99%